2017
DOI: 10.1016/j.urolonc.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant pelvic radiation is associated with improved survival and decreased disease recurrence in pelvic node-positive penile cancer after lymph node dissection: A multi-institutional study

Abstract: Adjuvant pelvic radiation is associated with improved survival and decreased recurrence in this population of patients with penile cancer with positive PLNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…Adjuvant radiotherapy is indicated for patients with a compromised surgical margin (recommendation, LE: 5), and for those with cN2 disease not receiving neoadjuvant treatment and undergoing inguinal and pelvic lymph-node dissection, if ≥ pN2 (recommendation, LE: 2b). Adjuvant radiotherapy improves overall survival in patients with advanced disease with lymph-node involvement (Tang et al 2017 ; Winters et al 2018 ) and decreases recurrence rates (Tang et al 2017 ). pT3–pT4N0 with free margins is not an indication for adjuvant radiotherapy in penile cancer (consensus, LE: 2b) as it does not improve oncological outcomes compared with surgery alone (Burt et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant radiotherapy is indicated for patients with a compromised surgical margin (recommendation, LE: 5), and for those with cN2 disease not receiving neoadjuvant treatment and undergoing inguinal and pelvic lymph-node dissection, if ≥ pN2 (recommendation, LE: 2b). Adjuvant radiotherapy improves overall survival in patients with advanced disease with lymph-node involvement (Tang et al 2017 ; Winters et al 2018 ) and decreases recurrence rates (Tang et al 2017 ). pT3–pT4N0 with free margins is not an indication for adjuvant radiotherapy in penile cancer (consensus, LE: 2b) as it does not improve oncological outcomes compared with surgery alone (Burt et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of AR may provoke lymphedema in patients who have already undergone extensive groin and pelvic dissection 29. However, AR was associated with improved survival and decreased recurrence in a recent multi-institution study of 92 patients who received AR for positive pelvic lymph nodes 7. AC has been recommended as an additional treatment option for such high-risk cases,8 as it is less likely to contribute to lymphedema and increase related morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the efficacy of oncological treatment to men with penile cancer is limited. Results from small non-randomized studies indicate that it may be possible to improve the prognosis with the use of chemotherapy and radiotherapy [10][11][12][13]. However, a systematic review in 2018 [14] found insufficient evidence for recommending adjuvant radiotherapy.…”
Section: Introductionmentioning
confidence: 99%